ENGLISH EDUCATIONAL MOODLE-BASED ENVIRONMENT ON ACTUALIZING PERSONALIZATION VIRTUAL COURSE - Prasetya, Rizky Eka; Nugraha, Novanda Alim Setya (Universitas Muhammadiyah Metro, 2022)
The study aims to explore, analyze, and determine the possibility of Moodle platform accommodating English learning personalization. The study applied a convergent parallel design mixed-method and was concerned with a quantitative survey and qualitative case study (deductive approach). The findings indicated and determined the personalization of English learning Moodle-based, and those elements included adjustable material and mechanism, concentrated instruction, component-based decisions, and English language learner observation. The adaptability Moodle system accommodated the personalization approach in learning English Moodle-based. The feature involved is isk, file, folder, IMS Content Package, Label, Page, URL (Resources) and Choice, Database, Feedback, Forum, Glossary, Lesson, (LTI) External tool, Quiz, SCORM, Wiki, Workshop (Activities). According to the findings, the Moodle environment became a relevant system to accommodate English pedagogy with a personalization approach. Online learning personalization choices range from simple settings to applications and Moodle capabilities to offer intelligent assistance. This scenario includes modifying developed on interactivity and communication Moodle settings